Fully Solution‐Processed Semi‐Transparent Perovskite Solar Cells With Ink‐Jet Printed Silver Nanowires Top Electrode (Solar RRL 2∕2018). Issue 2 (8th February 2018) - Xie, Menglan; Lu, Hui; Zhang, Lianping; Wang, Jie; Luo, Qun; Lin, Jian; Ba, Lixiang; Liu, Hong; Shen, Wenzhong; Shi, Liyi; Ma, Chang‐Qi
Abstract : Perovskite solar cells have attracted much attention in the last few years due to their high power conversion efficiency (PCE) and solution based printing process compatibility. The preparation of a metal electrode with printing process is, however, a big challenge for perovskite solar cells, which is, on the one hand, due to the sensitivity of the perovskite film, and on the other hand, due to the poor interconnection between electrode buffer layer and the printed metal electrode. This problem was solved in article number 1700184 by Qun Luo, Jian Lin, Liyi Shi, Chang‐Qi Ma and co‐workers, by inserting a thin polyethylenimine (PEI) layer. Therefore, achieving high performance semi‐transparent perovskite solar cells with ink‐jet printed silver nanowire top electrode.